Educational tracks of Russian youth in system of education (on state statistics 2000-2017) - Galina, Cherednichenko (Advances in Social Sciences Research Journal, 2019)
Unlike in developed countries, there are few indicators in the Russian education statistics concerning youth educational tracks between its successive levels, from the basic to the higher one. Since 2014, the Ministry of Education and Science of Russia has published raw statistical data, inaccessible to readers as they are, on its website. The author has calculated and analyzed a number of relevant indicators from this and other sources. The evaluation is focused on the 2000-2017 changes in the enrollment in Basic and Secondary Schools and subsequent distribution of students across educational tracks; enrollment in Secondary Vocational Education (mid-level specialist and skilled worker programs), distribution of students across modes of study and educational attainment at admission; enrollment in Higher Education Institutions across modes of study, types of Higher Education Institutions ownership and educational attainment at admission to full-time and extramural classes. The data on the number of relevant age cohorts inform the analysis.